THE EFFECT OF READING STRATEGIES BY IRAQI INTERMEDIATE EFL LEARNERS AND THEIR CONSEQUENCES ON READING COMPREHENSION: A CASE STUDY OF MISSAN HIGH SCHOOLS - Hussein, Hassan Jabbar; Jabbar, Waleed Khazaal (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2022)
This investigated effect of reading strategies by Iraqi Intermediate EFL learners and their consequences on reading comprehension . The population selected for this experimental study was students of grade five at Missan high school in Iraq. The students were all male. In addition sixty EFL teachers also participated in the study. 140 students were selected randomly. They were divided into control groups, each group 70 learners. Apart from this a list of reading strategies was distributed among six hundred fifth grade high school learners to see which strategy was applied more. A placement test, a reading comprehension test, and a strategies questionnaire were used as instruments. Then reading strategies, (Predicting, Prior knowledge, Graphic organizers, Summarizing, Note taking, Glossary, Skimming/scanning, and asking questions) were applied by teachers to the experimental group. After 10 weeks of instruction a post test was carried out. The result showed that the strategies applied by the teachers and learners were rather different. The instructors used Asking Questions (22%), Skimming / Scanning (21%), Summarizing (19%) and Graphic Organizers (14%). Meanwhile, learners used more than all of all the Glossary, then it went to Note Taking, Summarizing and Skimming / Scanning by 23%, 20%, 18%, and 17%, and the use of other strategies were 10% or less. Also, the similarity of the two groups of instructors and learners was non-use or the negligible use of prediction. The result of study revealed that reading strategies were effective on language learners.